2012
DOI: 10.1007/s10705-012-9513-1
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the nitrogen from fertilizers in field-grown maize

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science+Business Media B.V.. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your work, please use the accepted author's version for posting to your own website or your institution's repository. You may further deposit the accepted author's version on a funder's repository at a funder's request, provided it is not made publicly available until 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 39 publications
5
14
0
6
Order By: Relevance
“…The percentage of applied N lost as NH 3 averaged 23% of applied N across the seven transplanted soils. This was almost double the losses measured from banding urea at the 5-cm depth at the same site (Rochette et al, 2013) but was consistent with two previous studies in Argentina examining NH 3 volatilization from subsurface-banded (2-cm depth) urea where losses were between 20 and 24% of applied N (Álvarez et al, 2007;Rimski-Korsakov et al, 2012). The values in the current study were also higher (approximately five times greater for the heavy-textured soils and 1.5 to 2 times greater for the medium-and coarse-textured soils) than an incubation study that used some of the same soils (Pelster et al, 2018).…”
Section: Influence Of Soil Physicochemical Propertiessupporting
confidence: 91%
“…The percentage of applied N lost as NH 3 averaged 23% of applied N across the seven transplanted soils. This was almost double the losses measured from banding urea at the 5-cm depth at the same site (Rochette et al, 2013) but was consistent with two previous studies in Argentina examining NH 3 volatilization from subsurface-banded (2-cm depth) urea where losses were between 20 and 24% of applied N (Álvarez et al, 2007;Rimski-Korsakov et al, 2012). The values in the current study were also higher (approximately five times greater for the heavy-textured soils and 1.5 to 2 times greater for the medium-and coarse-textured soils) than an incubation study that used some of the same soils (Pelster et al, 2018).…”
Section: Influence Of Soil Physicochemical Propertiessupporting
confidence: 91%
“…These N contents can be taken as the usual values at these locations and sowing dates. We assumed an exponentially decreasing N distribution with depth following reports in the literature (Rimski-Korsakov et al 2012). To parameterize water availability at sowing, we relied on the qualitative assessment that farmers did at sowing.…”
Section: Mechanistic Modeling: Ceres-maizementioning
confidence: 99%
“…Rochette et al [53] reported that the impact of urea application rate on the nitrogen loss in the form of ammonia (NH 3 ) is variable as shown in Table 4 [54][55][56][57][58][59][60][61][62][63][64]. The large variability in the results reported from several studies has been due to the nonlinear response of the ammonia to variation in pH and the availability of ammonia in the soil.…”
Section: Ammonia Volatilizaitonmentioning
confidence: 99%